Bone marrow‐derived mesenchymal stem cells promote Helicobacter pylori‐associated gastric cancer progression by secreting thrombospondin‐2. (25th August 2021) - Shi, Huiying; Qi, Cuihua; Meng, Lingjun; Yao, Hailing; Jiang, Chen; Fan, Mengke; Zhang, Qin; Hou, Xiaohua; Lin, Rong
Abstract: Objectives: Bone marrow‐derived cells (BMDCs), especially mesenchymal stem cells (MSCs), may be involved in the development of Helicobacter pylori ‐associated gastric cancer (GC) in mice, but the specific mechanism remains unclear, and evidence from human studies is lacking. Materials and Methods: To verify the role of BM‐MSCs in H pylori ‐associated GC, green fluorescent protein (GFP)‐labelled BM‐MSCs were transplanted into the subserosal layers of the stomach in a mouse model of chronic H pylori infection. Three months post‐transplantation, the mice were sacrificed, and the gastric tissues were subjected to histopathological and immunofluorescence analyses. In addition, we performed fluorescence in situ hybridization (FISH) and immunofluorescence analyses of gastric tissue from a female patient with H pylori infection and a history of acute myeloid leukaemia who received a BM transplant from a male donor. Results: In mice with chronic H pylori infection, GFP‐labelled BM‐MSCs migrated from the serous layer to the mucosal layer and promoted GC progression. The BM‐MSCs differentiated into pan‐cytokeratin‐positive epithelial cells and α‐smooth muscle actin‐positive cancer‐associated fibroblasts (CAFs) by secreting the protein thrombospondin‐2. FISH analysis of gastric tissue from the female patient revealed Y‐chromosome‐positive cells. Immunofluorescence analyses further confirmed that Y‐chromosome‐positive cells showed positive BM‐MSCs marker. These results suggested that allogeneic BMDCs, including BM‐MSCs, can migrate to the stomach under chronic H pylori infection. Conclusions: Taken together, these findings imply that BM‐MSCs participate in the development of chronic H pylori ‐associated GC by differentiating into both gastric epithelial cells and CAFs. Abstract : Bone marrow mesenchymal stem cells transplanted in mice with chronic H pylori infection gradually migrate from the subserosa to the mucosa and secret THBS2 protein to promote the occurrence and development of gastric cancer.